1996
DOI: 10.1029/96jc00506
|View full text |Cite
|
Sign up to set email alerts
|

Near‐surface circulation of the Nordic seas as measured by Lagrangian drifters

Abstract: In the period June 1991 to August 1993, 107 Argos tracked, drifters drogued to 15 m depth, were released in the Nordic seas (or Greenland, Iceland, and Norwegian Seas). The drifter movements revealed the strong and spatially confined current systems along the surface salinity fronts of the Iceland‐Faroe Frontal zone and of the Norwegian coast and along the continental margins and their extensions to the Barents Sea and Spitsbergen. The Norwegian Atlantic Current is composed of three distinct streams (two conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
204
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(238 citation statements)
references
References 26 publications
30
204
2
1
Order By: Relevance
“…The model forecast fails to ever reach a crossover time for the entire span of the available prediction. During the study period the average decorrelation times of the drifter velocities was found to be 1.2 days (not shown) in approximate agreement with Poulain et al (1996), LaCasce (2008), Döös et al (2013), and Lumpkin and Johnson (2013). This time scale is very similar to the e-folding time scale of persistence (black line in Figure 2a).…”
Section: Global Summarysupporting
confidence: 67%
“…The model forecast fails to ever reach a crossover time for the entire span of the available prediction. During the study period the average decorrelation times of the drifter velocities was found to be 1.2 days (not shown) in approximate agreement with Poulain et al (1996), LaCasce (2008), Döös et al (2013), and Lumpkin and Johnson (2013). This time scale is very similar to the e-folding time scale of persistence (black line in Figure 2a).…”
Section: Global Summarysupporting
confidence: 67%
“…The model also produces a mean broad anticyclone near the center of the Greenland Basin, which is a strong feature. Although float data (Poulain et al 1996) and current observations (Oliver and Heywood 2003) suggest that the local flow often opposes the largerscale mean circulation, it is doubtful that such a strong mean feature exists in the real Greenland Sea. Figure 7b shows that EKE is greatest where there are strong density gradients and weak topographic gradients.…”
Section: Fieldsmentioning
confidence: 99%
“…Dashed arrows indicate currents that are either less well established by observations or less permanent. Studies on which the schematic is based include results from a tracer release experiment (Messias et al 2008), observations from floats (Poulain et al 1996;Gascard et al 2002;Jakobsen et al 2003), moored and lowered current meters (Woodgate et al 1999;Fahrbach et al 2001;Oliver and Heywood 2003), hydrographic observations (Quadfasel and Meincke 1987), and modeled reconstructions of the circulation of the Nordic seas (Nøst and Isachsen 2003;Eldevik et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…The NCC transports 1-2 Sv northwards from inflow across 61 • N, with variability also 1-2 Sv -current variance is 0.01-0.02 m 2 s −2 (Poulain et al, 1996). NCC salinity (reduced by Baltic outflow) is less than 33 at 61 • N. Despite much riverine freshwater (greatly exceeding precipitation-evaporation), the salinity increases to about 34 off northern Norway as Atlantic water is entrained.…”
Section: Norwaymentioning
confidence: 99%